(571) Economic Policy and Planning in the Hungarian`s People Republic السياسة الاقتصادية والتخطيط في جمهورية المجر الشعبية - Borgan, Joseph (معهد التخطيط القومى, 2024)
The study explores the evolution of the concepts of plan, planning, planning systems, and planned economy in international political-economic literature and economic management practices. It highlights the varied interpretations of these concepts across different socio-economic systems, with distinct applications in socialist, developing, and capitalist countries, and unique models such as the Dutch and French planning systems compared to those of Egypt, India, or Nigeria. The study also examines the scientific and practical advancements in planning, emphasizing accumulated experiences that enhanced understanding of the relationship between planning and real economic processes. Furthermore, it discusses the refinement of economic policy priorities and the development of tools and methodologies to effectively implement economic management strategies